Economic integration and development : has regionalism delivered for developing countries? - Kreinin, Mordechai Elihau; Plummer, Michael G. (Cheltenham, UK ; Northampton, MA : Edward Elgar Pub., 2002)
This book leads to three important policy conclusions. First, in designing preferential trading arrangements, developed countries should recognize and attempt to minimize the possible discriminating effect on developing countries; second, the developing countries have an abiding interest in the success of WTO negotiations that would minimize the discrimination against them of regional groupings in Europe and North America; and third, any customs unions or free-trade areas among the developing countries themselves should be outward looking if they are to enhance the welfare of developing countries.
Includes index.
Includes bibliographical references (p. 151-159).
osc 05/09/2016
Loans
Keywords: Regional Integration; Trade blocs; International economic relations; Developing countries